Gemcitabine, lycorine and oxysophoridine inhibit novel coronavirus (SARS-CoV-2) in cell culture - Ya-Nan Zhang; Qiu-Yan Zhang; Xiao-Dan Li; Jin Xiong; Shu-Qi Xiao; Zhen Wang; Zhe-Rui Zhang; Cheng-Lin Deng; Xing-Lou Yang; Hong-Ping Wei; Zhi-Ming Yuan; Han-Qing Ye; et al. (Emerging Microbes and Infections)
The emerging SARS-CoV-2 infection associated with the outbreak of viral pneumonia in China is ongoing worldwide. There are no approved antiviral therapies to treat this viral disease. Here we examined the antiviral abilities of three broad-spectrum antiviral compounds gemcitabine, lycorine and oxysophoridine against SARS-CoV-2 in cell culture. We found that all three tested compounds inhibited viral replication in Vero-E6 cells at noncytotoxic concentrations. The antiviral effect of gemcitabine was suppressed efficiently by the cytidine nucleosides. Additionally, combination of gemcitabine with oxysophoridine had an additive antiviral effect against SARS-CoV-2. Our results demonstrate that broad-spectrum antiviral compounds may have a priority for the screening of antiviral compounds against newly emerging viruses to control viral infection.